2015
DOI: 10.1051/0004-6361/201424626
|View full text |Cite
|
Sign up to set email alerts
|

Rotational modulation of the linear polarimetric variability of the cool dwarf TVLM 513−46546

Abstract: Aims. We aim to monitor the optical linear polarimetric signal of the magnetized, rapidly rotating M8.5 dwarf TVLM 513−46546. Methods. R-and I-band linear polarimetry images were collected with the Andalucía Faint Object Spectrograph and Camera (ALFOSC) instrument of the 2.56-m Nordic Optical Telescope (NOT) on two consecutive nights, covering about 0.5 and four rotation cycles in the R and I filters, respectively. We also obtained simultaneous intensity curves by means of differential photometry. The typical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Only a handful of UCDs have data sets that allow the optical and radio variability (either bursts or non-bursting periodic variatons) to be phased. While the radio and optical maxima of TVLM 513-46546 are significantly out of phase (Wolszczan & Route 2014;Miles-Páez et al 2015), there is a hint that the millimeter and optical maxima may occur at the same phase (Williams et al 2015b). The radio and optical maxima of NLTT 33370 B are also significantly Figure 4: [From Williams et al (2014).…”
Section: Multi-wavelength Correlationsmentioning
confidence: 98%
“…Only a handful of UCDs have data sets that allow the optical and radio variability (either bursts or non-bursting periodic variatons) to be phased. While the radio and optical maxima of TVLM 513-46546 are significantly out of phase (Wolszczan & Route 2014;Miles-Páez et al 2015), there is a hint that the millimeter and optical maxima may occur at the same phase (Williams et al 2015b). The radio and optical maxima of NLTT 33370 B are also significantly Figure 4: [From Williams et al (2014).…”
Section: Multi-wavelength Correlationsmentioning
confidence: 98%
“…It has been shown by de Kok et al (2011) that such patchy atmospheres can lead to time-varying polarimetric signals with amplitudes greater than 0.1%. Indeed, Miles-Páez et al (2015) found observational evidence that the polarimetric variability of the cool dwarf TVLM 51346546 correlates with rotation. At the same time, detections of photometric variability and polarized emission have not been shown to be statistically correlated (e.g., Sengupta & Marley 2010;Miles-Páez et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…These condensates, sometimes referred to as "dusty" particles that can be or-E-mail: ppaez@uwo.ca ganized into "clouds", are expected to produce linear polarization at optical and near-infrared wavelengths via scattering processes (Sengupta & Krishan 2001;de Kok et al 2011). Observations reveal that linear polarization is measurable in some late-M and L dwarfs, which show typical polarimetric degrees smaller than 1% in the I-and J-bands (Ménard et al 2002;Zapatero Osorio et al 2005;Goldman et al 2009;Zapatero Osorio et al 2011;Miles-Páez et al 2013, 2015. Because the net polarization of a purely spherical atmosphere is zero, the linear polarimetry detections are usually explained by the asymmetries introduced by rotation-induced oblateness and/or patchy, non-uniform distribution of atmospheric condensates.…”
Section: Introductionmentioning
confidence: 99%